2016
DOI: 10.1002/ajp.22525
|View full text |Cite
|
Sign up to set email alerts
|

Maternal effects on offspring stress physiology in wild chimpanzees

Abstract: Early life experiences are known to influence hypothalamic-pituitary-adrenal (HPA) axis development, which can impact health outcomes through the individual's ability to mount appropriate physiological reactions to stressors. In primates, these early experiences are most often mediated through the mother and can include the physiological environment experienced during gestation. Here, we investigate stress physiology of dependent offspring in wild chimpanzees for the first time and examine whether differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 80 publications
(91 reference statements)
2
25
1
Order By: Relevance
“…The effects appear to depend on the severity and duration of prenatal stress, as well as the timing of HPA and behavioural assessment. 19 Similar results have been reported in a model of repeated stress during pregnancy in guinea pigs where juvenile male offspring exhibited lower concentration of basal cortisol both in plasma and FGM. 14 Infants whose mothers experienced high anxiety in late gestation exhibited an increased cortisol response at 5 weeks but reduced responses at 2 months and 1 year.…”
Section: Hpa Functionsupporting
confidence: 81%
See 1 more Smart Citation
“…The effects appear to depend on the severity and duration of prenatal stress, as well as the timing of HPA and behavioural assessment. 19 Similar results have been reported in a model of repeated stress during pregnancy in guinea pigs where juvenile male offspring exhibited lower concentration of basal cortisol both in plasma and FGM. 14 Infants whose mothers experienced high anxiety in late gestation exhibited an increased cortisol response at 5 weeks but reduced responses at 2 months and 1 year.…”
Section: Hpa Functionsupporting
confidence: 81%
“…sGC is a substrate for placental P-gp that decreases the transfer of sGC across the placenta. 80 In another study, restraint stress (gestational days [14][15][16][17][18][19][20][21] F I G U R E 1 Effects of maternal and paternal stress or glucocorticoid exposure. 73 Interestingly, previous rodent studies have shown that chronic prenatal stress results in increased DNA methylation at multiple CpG sites within the placental Hsd11b2 gene promoter, resulting in a down-regulation of placental transcription.…”
Section: Mechanis Ms Of Maternal Prog R Ammingmentioning
confidence: 99%
“…There is however evidence for some genetic predisposition of glucocorticoid excretion mechanisms (Linkowski et al, 1993;Oswald et al, 2004;Pflüger et al, 2016). Furthermore, a multitude of species has prolonged phases of intensive maternal care (e.g., Purvis and Harvey, 1995), rendering priming of glucocorticoid excretion patterns possible (e.g., Plotsky and Meaney, 1993, but see Aizer et al, 2015;Berghänel et al, 2016;Murray et al, 2016;McCormick et al, 2017). Therefore, exposure to differential levels of parental care and differences in genetic makeup could generate glucocorticoid trait repeatability among adult individuals in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Chimpanzees are an interesting species to study repeatability of urinary cortisol excretion and urinary cortisol reaction norms as infants are nursed by their mothers for around 4 years and carried and cared for even longer (Boesch and BoeschAchermann, 2000), rendering maternal priming of the HPA axis possible. Factors affecting glucocorticoid levels, such as circadian rhythms (Muller and Lipson, 2003), dominance rank (e.g., Muller and Wrangham, 2004;Anestis, 2005;Anestis et al, 2006;Muehlenbein and Watts, 2010), social dynamics (e.g., Fraser et al, 2008;Emery Thompson et al, 2010;Wittig et al, 2016), and maternal care (Murray et al, 2016) are well-studied in this species. This allows for an informed decision on potential control factors in statistical models and a sound biological interpretation of different patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation